Optical emission spectroscopy of plasma of underwater electric spark discharges between metal granules - Tmenova, T.A.; Veklich, A.N.; Boretskij, V.F.; Cressault, Y.; Valensi, F.; Lopatko, K.G.; Aftandilyants, Y.G. (Вопросы атомной науки и техники, 2017)
This paper presents series of experiments carried out with granules of Cu, Fe, Mn and Mo. Optical emission spectroscopy techniques were applied for research of the emission spectra of corresponding elements and improvement of the diagnostics of such plasma. Excitation temperature of plasma of underwater spark discharges between copper granules was determined using Boltzmann plot technique. The electron density of the plasma was estimated from broadening of hydrogen Hα line.